ASPEK SOSIOLOGI SASTRA DALAM NOVEL MENGGAPAI MATAHARI KARYA DERMAWAN WIBISONO - Ryan Hidayat (Universitas Negeri Makassar, 2017)
The Novel Analysis Menggapai Matahari created by Dermawan Wibisono viewed from the sociology aspect of literary. The purpose of this research is to described the aspects of sociology the work of literature in Menggapai Matahari. The methodology used in this research was a method of from the analysis of the contents of the descriptive. The novel have been analyzed based on the aspect of sociology literature, (1 ) the element of a social system: a political system as many as 3 points, a system of belief as many as 7 points, the economic system as many as 2 points, and the system of education as many as 7 points, (2) value system as many as 2 points and a system of an idea as many as 3 points , and (3) surveillance equipment sent to the culture as many as 3 points.